2015
DOI: 10.3892/or.2015.4276
|View full text |Cite
|
Sign up to set email alerts
|

Silencing β-linked N-acetylglucosamine transferase induces apoptosis in human gastric cancer cells through PUMA and caspase-3 pathways

Abstract: Abstract. β-linked N-acetylglucosamine (GlcNAc) is a monosaccharide that is catalyzed by O-GlcNAcylation transferase (OGT) to bind serine or threonine hydroxyl moieties of numerous nuclear and cytoplasmic proteins. Recent studies have shown that O-GlcNAcylation is elevated in various cancer types, which is associated with oncogenesis and tumor progression. However, whether OGT is expressed and/or plays a role in gastric cancer is unknown. In the present study, we used qPCR to determine that OGT mRNA levels are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Moreover, we found that miR-483 can suppress total protein O-GlcNAcylation in gastric cancer cells through directly targeting OGT. Our data are consistent with previous studies which showed that down-regulation of OGT inhibited cell growth and invasion of gastric cancer cells in vitro [32,33]. Our results reveal that miR-483 is critical in controlling the protein O-GlcNAcylation levels and regulating the proliferation and invasion potential of gastric cancer cells.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, we found that miR-483 can suppress total protein O-GlcNAcylation in gastric cancer cells through directly targeting OGT. Our data are consistent with previous studies which showed that down-regulation of OGT inhibited cell growth and invasion of gastric cancer cells in vitro [32,33]. Our results reveal that miR-483 is critical in controlling the protein O-GlcNAcylation levels and regulating the proliferation and invasion potential of gastric cancer cells.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have correlated expression of OGT and chemotherapy sensitivity. OGT silencing increases the sensitivity to 5-FU of BCG-823 gastric cancer cell line by enhancing expression of p53 upregulated modulator of apoptosis (PUMA) and caspase-3 pro-apoptotic proteins [ 159 ]. In this sense, Pepe et al showed in HepG2 hepatoblastoma cells that OGT stabilizes the transcriptional complex β-catenin/upstream stimulatory factor 1 (USF1) at the promoter of miR-483-3p, a microRNA responsible for transcription downregulation of PUMA [ 160 ].…”
Section: Glycosylation Alterations In Colorectal Cancer Cells and Resmentioning
confidence: 99%
“…Our data also revealed that not only GNB2L1, but its O-GlcNAcylation as well, was important for EMT in chemoresistance. It is well-known that O-GlcNAcylation and its transferase OGT was elevated in gastric cancer and involved in the survival of gastric cancer cells [ 26 ]. And a growing amount of studies supported the critical roles of O-GlcNAcylation in gastric cancer metastasis [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%